Hypothalamic Leucine Metabolism Regulates Liver Glucose Production - Su, Ya (American Diabetes Association, 2012)
Amino acids profoundly affect insulin action and glucose metabolism in mammals. Here, we investigated the role of the mediobasal hypothalamus (MBH), a key center involved in nutrient-dependent metabolic regulation. Specifically, we tested the novel hypothesis that the metabolism of leucine within the MBH couples the central sensing of leucine with the control of glucose production by the liver. We performed either central (MBH) or systemic infusions of leucine in Sprague-Dawley male rats during basal pancreatic insulin clamps in combination with various pharmacological and molecular interventions designed to modulate leucine metabolism in the MBH. We also examined the role of hypothalamic ATP-sensitive K(+) channels (K(ATP) channels) in the effects of leucine. Enhancing the metabolism of leucine acutely in the MBH lowered blood glucose through a biochemical network that was insensitive to rapamycin but strictly dependent on the hypothalamic metabolism of leucine to α-ketoisocaproic acid and, further, insensitive to acetyl- and malonyl-CoA. Functional K(ATP) channels were also required. Importantly, molecular attenuation of this central sensing mechanism in rats conferred susceptibility to developing hyperglycemia. We postulate that the metabolic sensing of leucine in the MBH is a previously unrecognized mechanism for the regulation of hepatic glucose production required to maintain glucose homeostasis.